Irish Urban Fictions (Literary Urban Studies,, 2018)
This collection is the first to examine how the city is written in modern Irish fiction. Focusing on the multi-faceted, layered, and ever-changing topography of the city in Irish writing, it brings together studies of Irish and Northern Irish fictions which contribute to a more complete picture of modern Irish literature and Irish urban cultural identities. It offers a critical introduction to the Irish city as it represented in fiction as a plural space to mirror the plurality of contemporary Irish identities north and south of the border. The chapters combine to provide a platform for new research in the field of Irish urban literary studies, including analyses of the fiction of authors including James Joyce, Roddy Doyle, Kate O'Brien, Hugo Hamilton, Kevin Barry, and Rosemary Jenkinson. An exciting and diverse range of fictions is introduced and examined with the aim of generating a cohesive perspective on Irish urban fictions and to stimulate further discussion in this emerging area.